2005
DOI: 10.1073/pnas.0502019102
|View full text |Cite
|
Sign up to set email alerts
|

Mountain gorilla tug-of-war: Silverbacks have limited control over reproduction in multimale groups

Abstract: To determine who fathers the offspring in wild mountain gorilla groups containing more than one adult male silverback, we genotyped nearly one-fourth (n ‫؍‬ 92) of the mountain gorillas (Gorilla beringei beringei) living in the Virunga Volcanoes region of Africa. Paternity analysis of 48 offspring born into four groups between 1985 and 1999 revealed that, although all infants were sired by within-group males, the socially dominant silverback did not always monopolize reproduction within his group. Instead, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
175
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(186 citation statements)
references
References 41 publications
9
175
2
Order By: Relevance
“…Excluding females' adult sons (known from long-term pedigree records) from the set of potential sires of those female's subsequent offspring did not alter these findings (B = 0.013, CI −0.043 to 0.063, P = 0.148). The B index in muriquis is much lower than that found for gorillas (7) and capuchins (8), and the fact that the lower limit of the 95% CI is less than zero indicates that the muriqui's paternity distribution does not deviate significantly from random expectations. The most successful male in the group sired only 18% of the infants sampled (n = 4); this value is far lower than the percentages reported for the most successful (and typically, high-ranking) males in the hierarchical societies of other patrilocal and matrilocal primates ( Table 1).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Excluding females' adult sons (known from long-term pedigree records) from the set of potential sires of those female's subsequent offspring did not alter these findings (B = 0.013, CI −0.043 to 0.063, P = 0.148). The B index in muriquis is much lower than that found for gorillas (7) and capuchins (8), and the fact that the lower limit of the 95% CI is less than zero indicates that the muriqui's paternity distribution does not deviate significantly from random expectations. The most successful male in the group sired only 18% of the infants sampled (n = 4); this value is far lower than the percentages reported for the most successful (and typically, high-ranking) males in the hierarchical societies of other patrilocal and matrilocal primates ( Table 1).…”
Section: Resultsmentioning
confidence: 75%
“…Paternity analyses have demonstrated that dominant males typically sire a disproportionate number of offspring, consistent with the priority of access that high rank often confers in competition over limited resources, including fertile females (2,(4)(5)(6)(7). In hierarchical societies, deviations from rank-biased paternity have been attributed to the mitigating effects of inbreeding avoidance (8) and to demographic, reproductive, and socioecological conditions that affect the number of male competitors, the monopolizability of fertile females, and the accessibility and effectiveness of coalition partners (3,(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Given this observed reproductive skew in favor of dominant males, it remains puzzling why subordinate males do not attempt takeovers more often. One possibility is that they are queuing for the alpha position (Kokko and Johnstone 1999;Cant and English 2006), as for example mountain gorillas (Bradley et al 2005) or spotted hyenas (East and Hofer 2001), but adult mortality rates are low, and sifaka life span may reach up to 30 years (Richard et al 2002). The potential success of this tactic can therefore not be evaluated with the available data.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional genetic study of gentle lemur (Hapalemur griseus) population, 91% of infants were also sired by a single resident male (Nievergelt et al 2002), whereas dominant males reaped 67% of all paternities in redfronted lemurs (Wimmer and Kappeler 2002), suggesting the existence of similar processes in other lemur taxa. Because the degree of male reproductive skew observed in this sifaka population equals or exceeds that of highly sexually dimorphic anthropoids living in highly polygynous systems, such as mountain gorillas (Bradley et al 2005), orang-utans (Utami et al 2002), mandrills (Charpentier et al 2005), patas monkeys (Ohsawa et al 1993), and red howler monkeys (Pope 1990), mechanisms other than exclusion and physical superiority are primary determinants of reproductive success of male sifaka. Perhaps dominant males are particularly effective at mate guarding at crucial times during the females' estrus (Clutton-Brock and Isvaran 2006) because their testes are clearly not adapted to intense sperm competition when examined from a comparative perspective (Kappeler 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation